Dynamic performance evaluation for a 3UPS-PRU parallel robot. (13th October 2016) - Zhao, Yongjie
This article deals with the methodology of the kinematic and rigid-body dynamic performance evaluation of the 3UP S-P RU (the underlined P denotes an actuating prismatic joint) parallel robot. The maximum input velocity index, the maximum driving torque index, and the maximum driving power index are formulated based on kinematic and rigid-body dynamic model, the theory of matrix norm and inequality. The physical meanings of the indices are the maximum input velocity, the maximum driving torque, and the maximum driving power, respectively, when the moving platform translates along the z -axis in the maximum linear acceleration a max, rotates about an arbitrary axis in the maximum angular acceleration α max, translates along the z -axis in the maximum linear velocity v max, and rotates about an arbitrary axis in the maximum angular velocityω max . Employing the worst-case criterion, the example of the kinematic and rigid-body dynamic performance evaluation of the 3UP S-P RU parallel robot is carried out using the presented indices. It is shown that the distribution trends of the maximum driving torque and the maximum driving power are roughly the same for the 3UP S-P RU parallel robot. The conclusions are provided at the end of the article.